Phosphodiesterase type 5 inhibitors usage and prostate cancer: a match-paired analysis - Machen, G. Luke; Rajab, M. Hasan; Pruszynski, Jessica; Coffield, K. Scott (Translational Andrology and Urology; Vol 6, No 5 (October 26, 2017): Translational Andrology and Urology (Management of Penile Cancer), 2017)
Background: To treat erectile dysfunction (ED), phosphodiesterase type 5 inhibitors (PDE5i) are commonly used. However, to date, only a few studies exist evaluate a possible effect on the incidence of prostate cancer. One such study completed by the authors’ institution suggested men who use PDE5i for ED may have a lower incidence of prostate cancer. This study was meant to address some of the shortcomings of the former study and further characterize the link between prostate cancer and PDE5i use. Methods: A retrospective, match-paired analysis was undertaken: 5,717 patients were identified between 2000 and 2011; a 1:2 match pair analysis ultimately identified 394 cases with cancer and 788 controls without cancer. Pairs were matched based on age, ethnicity, and PSA value. Results: No correlation existed between PDE5i use and prostate cancer [OR 1.02, 95% confidence interval (CI): 0.78–1.35, P=0.8842] or diabetes mellitus and prostate cancer (OR 1.12, 95% CI: 0.84–1.48, P=0.4499). A statistically significant correlation was demonstrated with PSA and prostate cancer (OR 1.48, 95% CI: 1.38–1.58, P